PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI MITRA DHUAFA (KOMIDA) CABANG ACEH TAMIANG - febi febi; Nailis Syuhada; Syamsul Rizal; Shelly Midesia (Jurnal Investasi Islam, 2019)
This study aims to determine the effect of service quality factors on the satiﬁ cation of members of the Koperasi Mitra Dhuafa (KOMIDA) Branch of Aceh Tamiang. In this study, the samples taken were 96 respondents. The researcher used quantitative research methods. The technique used in this study is simple random sampling. The type of data used in this study are primary data and secondary data. The data analysis technique used in this study is the classical assumption test analysis, multiple linear regression, and hypothesis testing. Partial result (t test) service quality factors that have a signiﬁ cant effect on member satisfaction consist of tangiable (BF) of 0.001 < 0.05 reliability (KH) of 0.006 < 0.05 assurance of 0.016 < 0.05 and emphaty of 0.001 < 0.05 while responsiveness (DT) of 0.275 > 0.05 did not signiﬁ cantly inﬂ uence member satisfaction. Simultaneous test result (test F) show a signiﬁ cance value of 0.000 < 0.05 which means that the factors of service quality, tangiable, reliability, responsiveness, assurance, and emphaty have a signiﬁ cant effect on satisfaction of members of the Koperasi Mitra Dhuafa (KOMIDA) Branch of Aceh Tamiang. Then the results of the R-Square test are 0.52 which means that 52% of member satisfaction can be explained by the factors of service quality consisting of tangiable, reliability, responsiveness, assurance, and emphaty while the remaining 48% is explained by other variables that are not entered in this study.